استعمال أنموذج (Altman) للإفلاس دالة لقياس الأداء دراسة تطبيقية في بعض الشركات المساهمة الخاصة العراقية - الجبوري, نصيف جاسم (Journal of Economics and Administrative Sciences, 2007)
Performance measures are a central component of management control system, making good planning and control decisions requires information about how different subunits of organizations have performed. To be effective, performance measures (both financial and nonfinancial) must also motivate managers and employees at all levels of organization to strive to achieve organization goals.To give aclear picture about performance must be used compound measure, that was best than single measure.Altman model can be used as a compound performance measure that measures the performance by tied a sum of variables, due to make weight for every variable to reach for performance.